2011
DOI: 10.1016/j.pain.2011.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced sensitization of transient receptor potential vanilloid 1 involves activation of hypoxia-inducible factor-1 alpha and PKC

Abstract: The capsaicin receptor, transient receptor potential vanilloid 1 (TRPV1), acts as a polymodal detector of pain-producing chemical and physical stimuli in sensory neurons. Hyperglycemia and hypoxia are two main phenomena in diabetes associated with several complications. Although many studies on streptozotocin-induced diabetic rats indicate that early diabetic neuropathy is associated with potentiation of TRPV1 activity in dorsal root ganglion neurons, its underlying mechanism and distinctive roles of hyperglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…The mechanism is involved in phosphorylation signaling elements downstream of this kinase. This point strongly implicates that PI3K or PKC in the signaling connecting TrkA and TRPV1 receptors are related to the activation of NGF receptor (Zhuang et al, 2004;Rathee et al, 2002;Violeta et al, 2011). Thus, we can infer that trkA-PI3K/PKC-TRPV1 signaling cascades are involved in NGF-induced sensitization.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…The mechanism is involved in phosphorylation signaling elements downstream of this kinase. This point strongly implicates that PI3K or PKC in the signaling connecting TrkA and TRPV1 receptors are related to the activation of NGF receptor (Zhuang et al, 2004;Rathee et al, 2002;Violeta et al, 2011). Thus, we can infer that trkA-PI3K/PKC-TRPV1 signaling cascades are involved in NGF-induced sensitization.…”
Section: Introductionsupporting
confidence: 51%
“…PKC activation is a downstream event of HIF-1␣ activation, which was inhibited by a HIF-1␣ inhibitor, 2-ME2 (Yu et al, 1998). PKC is known to be associated with potentiation of TRPV1 by direct phosphorylation (Violeta et al, 2011) or by recruitment of a pool of vesicular receptors to the plasma membrane via soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-dependent exocytosis (Morenilla-Palao et al, 2004). Thus, 2-ME2 could attenuate TRPV1 phosphorylation through inhibiting PKC activation.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that hypoxia increases the sensitivity of TRPV1 channels in vitro (Ristoiu et al . ), activates eNOS and stimulates nitric oxide production (Vanin et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…c [20]. Another recent study showed facilitation of TRPV1 activity by chronic hypoxia combined with hyperglycemia [21]. In this study, TRPV1 activity was functionally upregulated via protein kinase C (PKC)e-and hypoxiainducible factor-1 alpha (HIF-1a)-dependent signaling pathway, without increases in protein expression.…”
Section: Introductionmentioning
confidence: 62%
“…The study by Ristoiu et al [21] is limited to chronic ([24 h) effect of hypoxia, and their measurements were performed under normoxic condition. In the study of anoxic effects on TRPV1, only D[Ca 2? ]…”
Section: Introductionmentioning
confidence: 99%